SPECT myocardial perfusion imaging for the assessment of left ventricular mechanical dyssynchrony - Chen, Ji (2011)
Phase analysis of gated single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) is an evolving technique for measuring LV mechanical dyssynchrony. Since its inception in 2005, it has undergone considerable technical development and clinical evaluation. This article reviews the background, the technical and clinical characteristics, and evolving clinical applications of phase analysis of gated SPECT MPI in patients requiring cardiac resynchronization therapy or implantable cardioverter defibrillator therapy and in assessing LV diastolic dyssynchrony.